(untitled) (Fiep Bulletin - online, 2014)
This essay analyses the relation among several identities of Physical Education professors from Uniplac and the research production as a cement element in university teaching. Considering that Brazilian culture was constructed by the miscegenation of several people, our objective is to indicate the influence of that miscegenation as a mediator among human body, culture and research production integrally contributing for the professors’ professional formation, more directly in Physical Education field. Through interviews with ten professors from Physical Education course, Uniplac, we could detach some subjects. It was possible to notice that professors are still developing a methodology based on knowledge transmission in classroom; however, most of the interviewed professors are awake about “changes” they need to do in their practices, specifically research and knowledge production in the university. Thus, it is essential to stimulate knowledge production, to be in a constant reconstruction of the praxis, innovating, calling into question and proving, and those elements should be present in the professional identity of Physical education professor.